Methods for measuring hydrogen balance in vacuum chamber of U-3M torsatron during plasma experiments - Pashnev, V.K.; Petrushenya, A.A.; Bondarenko, V.N.; Sorokovoy, E.L.; Ponomarenko, N.P.; Ozherelyev, F.I. (Вопросы атомной науки и техники, 2017)
The experimental method was developed for evaluation of a hydrogen particle flux balance over a wide range of operating conditions in the Uragan-3M torsatron (U-3M) in the course of RF discharges. Standard pressure gauges were tested for measurement of non-stationary hydrogen pressure in the U-3M vacuum chamber. The average lifetime of hydrogen ions was determined for each operation mode of U-3M. Разработана экспериментальная методика оценки баланса потоков частиц водорода во время ВЧ-разрядов в торсатроне Ураган-3М (У-3М) в широком диапазоне рабочих параметров. Для измерения нестационарного давления водорода в вакуумной камере У-3М были апробированы стандартные датчики давления. Для каждого из рабочих режимов работы У-3М было определено среднее время жизни ионов водорода. Розроблено експериментальну методику оцінки балансу потоків частинок водню під час ВЧ-розрядів у торсатроні Ураган-3М (У-3М) в широкому діапазоні робочих параметрів. Для вимірювання нестаціонарного тиску водню у вакуумній камері У-3М були апробовані стандартні датчики тиску. Для кожного з робочих режимів У-3М було визначено середній час життя іонів водню.